2019
DOI: 10.17511/jopm.2019.i11.15
|View full text |Cite
|
Sign up to set email alerts
|

Study of abnormal haemoglobin variants in patients of anaemia using high performance liquid chromatography (HPLC) in Gujarat, India

Abstract: Introduction: Haemoglobinopathies are the most common inherited red cell disorders worldwide. Identification of these disorders is immensely important epidemiologically, for early diagnosis, improved management protocols and prevention of disease in upcoming generation. Our aim is to study the abnormal haemoglobin variants in patients of anaemia using High Performance Liquid Chromatography (HPLC) BIO-RAD D-10 Dual Program analyser in Vadodara region of Gujarat. Methods: A total of 1890 cases of patient's with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The third most commonest hemoglobinopathy that was detected in the total population of 29,293 patients within the 14 studies was of Hb E. Hb E constituted about 18.9% of hemoglobinopathies. Except for the reports of Sachdev et al [ 1 ], Shrivastav et al [ 3 ], Bhalodia et al [ 6 ], Sarvaiya and Chauhan [ 10 ], Shankar et al [ 12 ], and Jain and Saxena [ 13 ], Hb E remained the third most common hemoglobin variant detected.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The third most commonest hemoglobinopathy that was detected in the total population of 29,293 patients within the 14 studies was of Hb E. Hb E constituted about 18.9% of hemoglobinopathies. Except for the reports of Sachdev et al [ 1 ], Shrivastav et al [ 3 ], Bhalodia et al [ 6 ], Sarvaiya and Chauhan [ 10 ], Shankar et al [ 12 ], and Jain and Saxena [ 13 ], Hb E remained the third most common hemoglobin variant detected.…”
Section: Reviewmentioning
confidence: 99%
“…However, there are studies where some of the hemoglobins and hemoglobin variants have not been reported from certain regions of India. The study by Alam et al [ 7 ], Shankar et al [ 12 ], and Jain et al [ 13 ] did not report the abnormal hemoglobins of Hb Q India, Hb J Meerut, Hb D Iran, Hb Lepore, and HPFH, respectively. Similarly, the studies by Alam et al [ 7 ], Raman et al [ 9 ], and Sarvaiya and Chauhan [ 10 ] have not reported the presence of Hb Q India, Hb J Meerut, and Hb D Iran.…”
Section: Reviewmentioning
confidence: 99%
“…The MCHCfor its etiologies includes the underlying causes of iron deficiency state, beta-thalassemia trait, hemoglobinopathies because of HB E, HB D, HB C, and many others. Such a situation of MCHC before being embarked for the treatment requires assessing the hemoglobin for its variants and detecting abnormal hemoglobin [3].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of MCHC is the iron replacement therapy if the iron deficiency is suspected as its cause. However, the therapeutic iron can produce harmfuleffects if the underlying pathology for MCHC is otherwise like, betathalassemia trait, sickle cell disease, or the other hemoglobinopathies [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation